Debate Centered Civics Education: Using AI to Teach Future Ready Skills and Better Prepare Students for College, Careers, and Civic Life - Grubaugh, Steven; Levitt, Greg (Technium Social Sciences Journal, 2025)
Debate-centered civics education is a powerful pedagogical approach that fosters future-ready skills such as critical thinking, communication, and problem-solving. In an era where artificial intelligence (AI) is reshaping education, integrating AI-driven tools into debate instruction has the potential to enhance student learning and engagement. This study explores the role of debate-centered civics education in preparing students for college, careers, and informed civic participation by utilizing AI to refine argumentation and analytical reasoning skills. The study is grounded in experiential learning theory (Dewey, 1938), social constructivism (Vygotsky, 1978), Bloom’s taxonomy (1956), deliberative democratic theory (Hogan et al., 2017), and connectivism (Siemens, 2005), all of which emphasize active learning and critical discourse as essential to intellectual and civic development. Through a case study methodology, this research examines how AI-enhanced debate programs impact student performance, civic engagement, and digital literacy. Data will be collected through classroom observations, AI-driven feedback analysis, and interviews with educators and students. Findings from this study will contribute to educational practice by providing insights into how debate-centered instruction can be optimized with AI tools to improve student argumentation and engagement. The results will also inform policy recommendations for integrating debate-based civics education into K-12 curricula to equip students with the skills necessary to navigate an increasingly digital and complex democratic landscape.